2022
DOI: 10.1021/acs.langmuir.1c03247
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Influenza A Virus–Target Membrane Fusion Interface With Synthetic DNA–Lipid Receptors

Abstract: Influenza A virus (IAV) binds to sialylated glycans on the cell membrane before endocytosis and fusion. Cell-surface glycans are highly heterogeneous in length and glycosylation density, which leads to variations in the distance and rigidity with which IAV is held away from the cell membrane. To gain mechanistic insight into how receptor length and rigidity impact the mechanism of IAV entry, we employed synthetic DNA−lipids as highly tunable surrogate receptors. We tethered IAV to target membranes with a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…By tuning the amount of cholesterol in vesicles, the study found that cholesterol does enhance the (hemi)­fusion efficiency by presumably stabilizing the hemifusion state but does not affect the fusion rate. To ensure the fusion event, the target vesicles can be loaded with a self-quenching concentration to monitor the pore formation, and the tether length between the target vesicles and viral particles can be modulated to study the effects of receptor length and flexibility …”
Section: Biosensing Techniques For Membrane Interfacial Studymentioning
confidence: 99%
“…By tuning the amount of cholesterol in vesicles, the study found that cholesterol does enhance the (hemi)­fusion efficiency by presumably stabilizing the hemifusion state but does not affect the fusion rate. To ensure the fusion event, the target vesicles can be loaded with a self-quenching concentration to monitor the pore formation, and the tether length between the target vesicles and viral particles can be modulated to study the effects of receptor length and flexibility …”
Section: Biosensing Techniques For Membrane Interfacial Studymentioning
confidence: 99%
“…To observe content mixing between virus and vesicle compartments, typically, a water-soluble dye is encapsulated at self-quenching concentration within the virus or target vesicle interior which turns on in fluorescence due to dilution upon fusion (14)(15)(16)(17). These assays have been popular because content label dyes like calcein and sulforhodamine B (SRB) are relatively inexpensive (an important practical consideration since only a small fraction of dye gets encapsulated during preparation of the target vesicles).…”
Section: Introductionmentioning
confidence: 99%
“…Tethered lipid bilayers have been developed to host membrane proteins in a fluid–lipid bilayer configuration while maintaining the stability, mobility, and controllability of planar supported lipid bilayers (SLBs). Despite these advantages, SLBs interact strongly with their substrates and are therefore often incompatible with integral membrane proteins that can bind to their substrates. Tethered lipid bilayers take advantage of chemical tethering to separate the model lipid membrane from solid supports, so membrane-associated proteins can function without interference. Various methods have been applied, including polymer tethers, protein tethers, tethered bilayer lipid membranes (tBLMs) with diphytanyl ethylene glycol anchors, and DNA–lipid conjugates, which have been used in a variety of self-assembled membrane structures by exploiting the well-defined DNA specificity and length. This superior controllability was demonstrated in a model system using the segregation pattern of mobile tethers, and in the study of membrane fusion .…”
Section: Introductionmentioning
confidence: 99%
“…This superior controllability was demonstrated in a model system using the segregation pattern of mobile tethers, and in the study of membrane fusion . The DNA-tethered lipid bilayers have been further developed to enable patterning, and to mimic the viral membrane fusion via synthetic DNA–lipid receptors . A wide range of analyses investigating ligand-gated ion channels, pore-forming peptides, and membrane pores can be conducted if the DNA-tethered lipid membrane fully covers an electrode surface.…”
Section: Introductionmentioning
confidence: 99%